Interaction of Electromagnetic H-wave with the thin Metal Film is Located on the Dielectric Substrate - Utkin А.І.; Yushkanov А.А. (Physics and Chemistry of Solid State, 2015)
Interaction of electromagnetic H-wave with thin metal film is located between two dielectric environments ε1, ε2 in the case of different incident angles of H-wave θ and in the case of different reflection coefficients q1 и q2 is calculated in this article. Behavior analysis of reflection coefficient R, transmission coefficient T and absorption coefficient A in the case of its frequency dependence y and variation dielectric permeability of its environments is done.